Optimasi Perolehan dan Karakterisasi Serbuk Mucilago Hibiscus rosa-sinensis L. (MHR) sebagai Binder Tablet - Imam Prabowo; Iqbal Julian Rianda Pradana Putra; Via Rifkia (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
This study aims to optimize the yield of MHR powder because the research conducted by Shah and Patel in 2010 was still very small, namely around 8%. Optimization was carried out by varying the soaking and heating times and then characterizing the MHR powder to test whether the MHR powder was a good candidate as a tablet binder. Characterization tests performed were organoleptic tests, particle size distribution, polysaccharide identification, swelling ratio, solubility, flow properties, viscosity, and water content. The most optimal MHR powder recovery was 1 hour of soaking time and 6 hours of heating time with a yield of 11.50 ± 1.40%. The results of the characterization of the MHR powder included: organoleptic test of the MHR powder was light brown, had a distinctive herbal odor and was tasteless, the particle size distribution test was in the range of 100-400 microns with the highest percentage of particles in the size of 186 μm, the swelling ratio was at 23 .47 ± 0.41, positive polysaccharide identification test, solubility was at 0.000426 ± 0.000034, viscosity was at 4520 ± 1224.42. Broadly speaking, MHR powder is a potential candidate as a tablet binder, that was proved from tablet formulation using MHR powder as binder resulted hardness, friability and disintegration time as well as formulation that using Avicel PH102 as binder.